Analysis Populations in Anti-Infective Clinical Trials: Whom to Analyze? - Evans, Scott (Stat Commun Infect Dis, 2018)
Investigators can choose to analyze different patient populations in clinical trials. The different analysis populations answer different types of research questions, estimate different quantities, and evaluate the robustness of the trial results. Various analysis populations have different strengths and weaknesses depending on the type of question being addressed and the potential for bias from the selection of various groups of trial participants. We discuss analysis populations in the context of anti-infective clinical trials.